Corporate social responsibility of mining industries. Issue 5 (14th September 2015) - Sharma, Deepankar; Bhatnagar, Priya
Abstract : Purpose: – This paper aims to examine the community development approaches of large-scale mining companies, with particular reference to how they may engender community dependency. Design/methodology/approach: – The paper begins with a review of corporate social responsibility (CSR) in the mining industry, corporate community initiatives and the problem of mining dependency at a national, regional and local levels. Findings: – It outlines some of the reasons why less-developed countries (LDCs) experience under-development and detrimental effects as a result of their linkages with industrialized countries. LDCs are not able to take advantage of advanced technology and management skills due to being relatively poor in capital and skills, and foreign technologies compete unfairly with and destroy local production techniques, creating a pool of unemployable "marginalized" people. Holder's of investments in LDCs demand annual returns for continued support – profits are taken out of the country or guaranteed by tax concessions. Unwillingness of foreign firms to train local people to take over management positions. Originality/value: – This paper explores how the need to address sustainability issues has affected communities, and whether community development initiatives have been effective in contributing to more sustainable communities.